Role of neutrophil extracellular traps in radiation resistance of invasive bladder cancer - Surashri Shinde-Jadhav (Nature Portfolio, 2021)
Radioresistance remains a challenge in the treatment of bladder cancer. In this study, the authors show in mice that radiation increases deposits of neutrophil extracellular traps (NETs) via a TLR4-dependent mechanism and that NETs-targeting strategies can improve the response to radiotherapy.